92 Reshaping the Diagnostic Pathways for Investigation of Haematuria During and After The COVID-19 Pandemic: Diagnostic Accuracy of Strategies for Detection of Bladder Cancer from The IDENTIFY Cohort Study. (4th May 2021) - Khadhouri, S; Gallagher, K; MacKenzie, K; Shah, T; Gao, C; Moore, S; Zimmermann, E; Edison, E; Jefferies, M; Nambiar, A; Mannas, M; Lee, T; et al.
Abstract: Introduction: Diagnostic haematuria services have been reduced due to the COVID-19 pandemic, compromising patient care, and necessitating a more pragmatic pathway. Method: The IDENTIFY study was an international, prospective, multicentre cohort study of over 11, 000 patients referred to secondary care for investigation of haematuria. Using this data, we developed strategies using combinations of imaging and cytology as triage tests to maximise cancer detection within a pragmatic pathway. Results: 8112 patients (74·4%) received an ultrasound or a CT urogram, with or without cytology. 5737 (70·7%) patients had visible haematuria (VH) and 2375 (29·3%) had non-visible haematuria (NVH). Diagnostic test performance was used to determine optimal age cut-offs for four proposed strategies. We recommended proceeding directly to transurethral resection of bladder tumour for patients of any age with positive triage tests for cancer. Patients with negative triage tests under 35-years-old with VH, or under 50-years-old with NVH can safely be discharged without undergoing flexible cystoscopy. The remaining patients may undergo flexible cystoscopy, with a greater priority for older patients to capture high risk bladder cancer. Conclusions: We suggest diagnostic strategies in patients with haematuria, which focus on detection of bladder cancer, whilst reducing the burden to healthcare services in a resource-limited setting.